Awareness Regarding Zoonotic Diseases among the Butchers of Proddatur, Kadapa Dist., A.P., India - Z.NAVEEN Prabhakar; M. Lokesh; M. Saidaiah; E.Sri Sai (Iranian Journal of Health, Safety and Environment, 2017)
Zoonotic diseases present an ongoing public health concern. Most human infections with zoonoses come from livestock, including pigs, chickens, cattle, goats, sheep and camels. Butchers constitute the high risk group in the transmission of zoonotic diseases. The educational status and awareness regarding the information, identification and transmission of zoonotic diseases among this high risk group, is critical in controlling the spread of zoonotic diseases. Hence, a study has been designed to evaluate the educational status, awareness among the butchers regarding the various zoonotic diseases and their modes of transmission and the effluent treatment methods followed by the butchers in and around Proddatur, Andhra Pradesh. The survey revealed that 86 percent of the butchers had high school education and most of them acquired this profession from their ancestors. 60 percent of the butchers were having awareness regarding the commonly occurring zoonotic diseases, 81 percent of butchers identified the disease by observing the lesions and were familiar with their control. Some of the butchers follow the hygienic practices and majority of them (81.4 %) were interested in attending training programmes pertaining to zoonotic diseases.